The conspiracy of life : meditations on Schelling and his time - Wirth, Jason M., 1963- (Albany, NY : State University of New York Press, 2003)
"The Conspiracy of Life offers a series of meditations on the philosophy of F.W.J. Schelling (1775-1854), a great - philosopher of life. Rather than construing him as a loopy mystic, or as an antiquated theologian, Jason M. Wirth attempts to locate Schelling as the belated contemporary of thinkers like Heidegger, Derrida, Bataille, Irigaray, Foucault, Deleuze, Levinas, and many others. As such, Schelling is already at the central nerve of current discussions concerning the crisis of truth; the primacy of the Good; the ecstatic nature of time; the nature of art; deep ecology; the world as an aesthetic phenomenon; comparative philosophy; the possibility of non-dialectical philosophy; radical evil; the haunting of philosophy; and the possibility of a philosophical religion."--Jacket
The nameless good -- Theos Kai pan -- Nature -- Direct experience -- Art -- Evil -- The haunting -- Peruṣottama.
Includes bibliographical references (pages 265-280) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Schelling, Friedrich Wilhelm Joseph von, -- 1775-1854.; Schelling, Friedrich Wilhelm Joseph von, -- 1775-1854; Schelling, Friedrich Wilhelm Joseph von -- 1775-1854; Schelling, Friedrich Wilhelm Joseph von; PHILOSOPHY -- History & Surveys -- Modern; Philosophie